Applying eco-visualisations of different interface formats to evoke sustainable behaviours towards household water saving. Issue 9 (1st September 2016) - Fang, Yu-Min; Sun, Meng-Shien
ABSTRACT: The shortage of water resources is a global issue. This study attempts to utilise eco-visualisation interface design to affect users' water-usage behaviour. Three interface proposals were designed in this study: numeric, water droplet (abstract symbol), and swimming fish (animated image). These three different interface formats range from abstract to figurative and from neutral to affective. A total of 93 subjects were divided into three groups and randomly performed designated dishwashing tasks twice. One of the tasks was completed without the assistance of any interface, whereas the other involved applying one of the three interface formats with eco-visualisations. In this study, the Self-Assessment Manikin scales, the System Usability Scale, and the Questionnaires for User Interaction Satisfaction were used to measure the emotional dimensions and perceived usability and to record the differences in water usage volume. The results indicated that the emotional valence evoked by the animated image interface was significantly higher than that by the numeric interface. The effect of the numeric interface formats on the subjects focused on emotional arousal, whereas other interfaces emphasised emotional valence. With the aid of the eco-visualisations of interface design, the evoked emotional response and enhanced usability could help improve sustainable behaviours towards water saving.